Factores psicosociales y estrategias de afrontamiento al estrés del cuidador familiar del adulto mayor dependiente en el hogar Padomi Essalud Trujillo 2010 - Correa Córdova, América María (2010)
This research study is a quantitative descriptive correlational cross-sectional study aimed to establish the relationship between coping with stress and psychosocial factors: perceived social support, role overload and level of knowledge of family caregiver dependent elderly at home. PADOMI. Hospital I Albrecht - ESSALUD. Trujillo, during the months of January to March 2010. The sample universe was composed of 80 family caregivers of dependent older adults in the household, selected according to established inclusion criteria. For data collection instruments were applied: Coping Strategies Inventory Stress Scale, Perceived Social Support Scale, Family Caregiver Burden Scale (Zarit) and Knowledge Level Test, considering the rights of anonymity and confidentiality. The data were processed in SPSS 15 and analyzed by the test of independence of criteria "Chi - square" as well as Pearson correlation to measure the degree of association between variables. The results indicate that 72.5% of family caregivers presented the strategy for coping with stress focused on the problem, 60% had minor roles on load, and 57.5% had a level of knowledge and 60% half an appropriate level of social support. Likewise, we found that psychosocial factors: perceived social support and role overload have a highly significant relationship with coping strategies to stress, however, the factor level of knowledge does not show a significant relationship with coping with stress.